MENCERMATI PASAR MODAL: PRESPEKTIF SYARIAH - Zaman, Qomarus (Fakultas Ekonomi, UIN Maliki Malang, 2009)
Hereinafter about appraisal to itself Moslem law stock market concept, namely related to stock as main instrument in Moslem law stock market, hence syara ' doesn't enable stock commerce. So also publishs stock with a purpose to adds company legal capital, buys stock with a purpose to investment and commercializes it to practice on (capital gain) from price difference (margin) be activity of batil in Islam. Concerning above problems, writer proposes things following: Firstly, writer mutuallies agree to that a company required legal capital must make a move at sector that is is not is against Islam and not related to lap. Second, to do investment at one particular company, an moslem investor must choose companys which its form fulfilling Islam criterion like syirkah inan, abdan, mudharabah, wujuh and mufawadhah. Third, supporting facilities for investment developed in Moslem law stock market shall which has fulfilled Islam criterion and mengikuti/disesuaikan with form of syirkah Islam, so that later there are no even little doubt at Moslem law stock market.